2016
DOI: 10.1080/13548506.2016.1220603
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and sociocultural determinants of psychological distress and quality of life among patients with psoriasis in a selected multi-ethnic Malaysian population

Abstract: Patients with psoriasis may have increased risk of psychological comorbidities. This cross-sectional study aimed at determining associations between sociocultural and socioeconomic factors with the Depression Anxiety Stress Scale (DASS) scores and the Dermatology Life Quality Index (DLQI) scores. Adult patients with psoriasis were recruited from a Dermatology outpatient clinic via convenience sampling. Interviews were conducted regarding socio-demographic factors and willing subjects were requested to complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
18
1
Order By: Relevance
“…In a study of Greek people with psoriasis, the mean DLQI score was 12.61 pts [37]. Kwan et al [38] reported a mean DLQI score of 6 pts. In their study, the DLQI scores for 31% of respondents corresponded to a severe deterioration of quality of life.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of Greek people with psoriasis, the mean DLQI score was 12.61 pts [37]. Kwan et al [38] reported a mean DLQI score of 6 pts. In their study, the DLQI scores for 31% of respondents corresponded to a severe deterioration of quality of life.…”
Section: Discussionmentioning
confidence: 98%
“…The literature reported different quality of life scores for different populations. 23 25 Cultural background of patients may explain these findings. Within the Arabic countries, a study from Kuwait reported impaired sexual activities in one-third of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sex; age (18–24, 25–34, 35–44, 45–54, 55–64, and 65 years and older); federal poverty level (<100%, ≥100%); education (<high school, high school/graduate‐equivalent degree, >high school); employment status (“Had job last week” and “No job last week, had job past 12 months” recoded as Employed/recently employed; “No job last week, “No job past 12 months” and “Never worked” recoded as Unemployed); and marital status (“Never married,” “Divorced or separated,” and “Widowed” recoded as Single; “Married,” and “Living with a partner” recoded as Married/cohabitation) were used as control variables in regression models. These variables were identified from existing literature (Borsje et al, ; Casetta et al, ; Etter, Prokhorov, & Perneger, ; Gadalla, ; Gorney & Long ; Haire‐Joshu, Morgan, & Fisher, ; Kozlowski, ; Kwan et al, ; Mickens, Ameringer, Brightman, & Leventhal, ; O'Loughlin, Dugas, O'Loughlin, Karp, & Sylvestre, ; Soneji et al, ; Tabak, Jodkowska, & Oblacinska, ; Tang, Castle, & Choong, ).…”
Section: Methodsmentioning
confidence: 99%